Do global ao local: a política de participação da família e suas repercussões na gestão da unidade escolar - Silva, Sheyla Aparecida de Moraes e (2006)
This work aims to research how the family participation can contribute for the democratisation of school management, trying to understand the different forms of family s participation within the schools, analysing the global politics materialised at the local place. This politics affect people at the same time that these people appropriate of this politics in different ways. We can see, here, the local and the global not as a duality, but as two levels that must be thinking articulately (TEIXEIRA, 2001:20). The research was developed in two schools chosen with the Secretary of Education of Juiz de Fora City, looking for a school that was developing a project of family s participation within the school systematically and another school that was not developing a project or specific practice of family s participation. The objective was to characterise both kind of school management. The schools chosen were the Escola Municipal Anísio Teixeira (EMAT) and the Escola Municipal Darcy Ribeiro (EMDR), respectively. It was possible to evidence in the study that the relation between democratic management and family s participation, sometimes, appears fragile. In the EMDR, antidemocratic practices were developed within this school, although the belief of school actors in some way, reinforced by the selectivity that signs the students ingress. Family s participation assumes, merely, a formal aspect, contributing for the constitution of an autocratic management centralised in the school s director. By the other hand, in the EMAT, the school s subjects recognised the importance of build their own territories through principles of justice and equality. So, the actions engagement combine with a democratic management characteristics, providing the real participation of the subjects in the decision process. In this way, it was possible to look for the intrinsically relation between the families in the school and the construction of a democratic management based on their real participation, considering the politic dimension of this participation, constituted by the appropriation and cultural reinterpretation by the school actors.